Ultrafast photonics applications of emerging 2D-Xenes beyond graphene - Zhang, Huanian; Sun, Shuo; Shang, Xinxin; Guo, Bo; Li, Xiaohui; Chen, Xiaohan; Jiang, Shouzhen; Zhang, Han; Ågren, Hans; Zhang, Wenfei; Wang, Guomei; Lu, Cheng; et al. (Nanophotonics (Berlin, Germany), 2022)
Driven by new two-dimensional materials, great changes and progress have taken place in the field of ultrafast photonics in recent years. Among them, the emerging single element two-dimensional materials (Xenes) have also received much attention due to their special physical and photoelectric properties including tunable broadband nonlinear saturable absorption, ultrafast carrier recovery rate, and ultrashort recovery time. In this review, the preparation methods of Xenes and various integration strategies are detailedly introduced at first. Then, we summarize the outcomes achieved by Xenes-based (beyond graphene) fiber lasers and make classifications based on the characteristics of output pulses according to the materials characterization and nonlinear optical absorption properties. Finally, an outlook of the future opportunities and challenges of ultrafast photonics devices based on Xenes and other 2D materials are highlighted, and we hope this review will promote their extensive applications in ultrafast photonics technology.